Virtual Care in Rhinology - Kristine A. Smith; Andrew Thamboo; Yvonne Chan; Christopher J. Chin; Megan Werger; Brian Rotenberg (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The SARS-CoV-2 (COVID) pandemic has resulted in an increase in virtual care. While some specialties are well suited to virtual care, Otolaryngology – Head and Neck Surgery could be limited due to reliance on physical examination and nasal endoscopy, including Rhinology. It is likely virtual care will remain integrated for the foreseeable future and it is important to determine the strengths and weaknesses of this treatment modality for rhinology. Methods A survey on virtual care in rhinology was distributed to 61 Canadian rhinologists. The primary objective was to determine how virtual care compared to in-person care in each area of a typical appointment. Other areas focused on platforms used to deliver virtual care and which patients could be appropriately assessed by virtual visits. Results 43 participants responded (response rate 70.5%). The majority of participants use the telephone as their primary platform. History taking and reviewing results (lab work, imaging) were reported to be equivalent in virtual care. Non-urgent follow up and new patients were thought to be the most appropriate for virtual care. The inability to perform exams and nasal endoscopy were reported to be significant limitations. Conclusion It is important to understand the strengths and limitations of virtual care. These results identify the perceived strengths and weaknesses of virtual care in rhinology, and will help rhinologists understand the role of virtual care in their practices. Graphical abstract